Methods in bioengineering : alternative technologies to animal testing - Maguire, Timothy J. (Timothy John); Novik, Eric (Artech House methods in bioengineering series., 2010)
Written and edited by recognized experts in the field, the new Artech House Methods in Bioengineering book series offers detailed guidance on authoritative methods for addressing specific bioengineering challenges. Offering a highly practical presentation of each topic, each book provides research engineers, scientists, and students with step-by-step procedures, clear examples, and effective ways to overcome problems that may be encountered. Providing alternatives to animal testing is one of the hottest topics in biomedical research, and this groundbreaking volume addresses this critical issues head on. This unique book presents techniques and methods at the forefront of scientific research that have the potential to replace certain whole animal tests. Moreover, this book provides a platform where other widely accepted techniques and scientific advancements can be collated into a concise set of methods that can be implemented within both academic and industrial communities.